Secure Electronic Payment: Proposed method for the growth of E-commerce in Bangladesh - Islam, Md. Monirul; Rashid, Harunur; Alam, Md. Golam Rabiul (Asian Business Review, 2015)
The innovations in technologies are changing the social, cultural and economic relationships in a vast variety of ways. Information technology has become a necessary tool for today’s organizations and banking industry is not an exception. Electronic commerce is rapidly growing modern business process in all over the world, but in Bangladesh it is increasing comparatively slower rate. Though Bangladesh was comparatively a late introducer of e-banking but now almost all the banks are providing internet banking to their customers. But what is important is the lack of comprehensive study of the e-payment security covering organizational and customers’ point of view. Considering the importance of secure e-payment to grow up e-commerce in Bangladesh this study was taken up. It was revealed from the survey that the customers’ and service providers main concern was security. E-banking service providers should have to ensure that online banking is safe and secure for every user in all kind of transactions. The Authors also proposed a secure e-payment model in general and on debit card and credit card to bring customers confidence on e-payment and increase the volume of e-commerce in the context of Bangladesh.